2012
DOI: 10.1007/s11136-012-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life measures in Arabic speaking populations: A systematic review on cross-cultural adaptation and measurement properties

Abstract: This review facilitates the selection among existing Arabic versions of generic HRQL for use in particular Arabic countries. However, each of the translated versions requires further investigation of measurement properties before more concrete recommendations could be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 28 publications
4
47
0
Order By: Relevance
“…In regard to construct validity, the results of this study clearly support and add to what has already been reported in the literature (Al Sayah, Ishaque, Lau, & Johnson, 2013). It adds to and boosts the strong conceptual structure of the various domains of the WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 85%
“…In regard to construct validity, the results of this study clearly support and add to what has already been reported in the literature (Al Sayah, Ishaque, Lau, & Johnson, 2013). It adds to and boosts the strong conceptual structure of the various domains of the WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 85%
“…Participating patients were asked to complete the validated WHOQOL-BREF [25], the validated PHQ-9 and the GAD-7 questionnaires [26,27]. The English versions, as well as the validated Arabic versions of both questionnaires were used [28].…”
Section: Participantsmentioning
confidence: 99%
“…Backward Translation: Accordingly, back-translator(s) should be professionals, native speakers of the source language and fluent in the target language (56,57). Preferably, they should have no prior knowledge of the original instrument (54,58), or any other language version of the instrument to avoid bias (59).…”
Section: Methodsmentioning
confidence: 99%